Safety and Efficacy of Anti-PD-1/PD-L1 Inhibitors Compared With Docetaxel for NSCLC: A Systematic Review and Meta-Analysis - Ma, Long; Jin, Gang; Yao, Keying; Yang, Yi; Chang, Ruitong; Wang, Wenhao; Liu, Jiawei; Zhu, Zijiang (Frontiers in Pharmacology, 2021)
Objective: To evaluate the efficacy and safety of anti-PD-1/PD-L1 Inhibitors versus docetaxel for non-small cell lung cancer by meta-analysis. Methods: Randomized controlled trials (RCTs) about anti-PD-1/PD-L1 Inhibitors versus docetaxel on the treatment of NSCLC were searched in CNKI, WF, VIP, PubMed, EMBASE, Cochrane Library, and Web of Science databases. Two reviewers independently screened literature, extracted data and evaluated the risk of bias of eligible studies. Meta-analysis was performed by RevMan5.3 software. Results: Compared with the use of docetaxel chemotherapy for NSCLC, the overall survival and progression-free survival of the anti-PD-1/PD-L1 Inhibitors regimen are better (overall survival: [HR= 0.73, 95%CI:0.69~0.77, P<0.00001], progression-free survival: [HR= 0.89, 95%CI:0.84~0.94, P<0.00001]), and lower incidence of treatment-related grade 3 or higher adverse events ([OR=0.21, 95% CI: 0.12~0.30, P<0.00001]). Conclusion: Compared with the docetaxel chemotherapy regimen, the anti-PD-1/PD-L1 Inhibitors has certain advantages in terms of efficacy and safety. the results still need to be confirmed by multi-center, large sample, and high-quality research.